Efecto del tiempo de temple en una aleación cuproaluminio cobre - 10% aluminio revenido a 400°c sobre la resistencia al desgaste, resistencia al impacto y dureza - Ortiz Cardenas, Walter Alfonso (2019)
In the present investigation the time of the temple has been studied in a copperaluminum alloy: copper - 10% aluminum heated to 900 ° C at the times of 1, 2, 3 and 4 hours, temple in water and tempered at 400 ° C for 1 hour, about wear resistance, impact resistance and hardness. For this purpose, discs with external diameter of 40 mm, internal diameter of 16 mm and thickness of 15 mm cast in sand mold were cast from where the tests for the wear test according to ASTM G77 standard were obtained; and square bars of 12 mm x 12 mm x 180 mm length cast in sand mold from where the tests were obtained for the Charpy impact test according to ASTM E23-98, and for the hardness test according to the ASTM E-norm. 140. It was determined that the copper alloy -10% molten aluminum and cast in sand mold, microstructurally, consists of alpha (α) and eutectoid (α + Υ2) phase and that after the temple at the time of study, tempered to 400 ° C the constant structure of phase alpha (α) and martensite abatement (β '). The results indicate that the temple time in the range of 1 to 4 hours at 900 ° C and the tempering at 400 ° C for 1 hour affects the wear resistance, impact resistance and hardness. In such a way that as the time of the temple increases in the range of 1 to 4 hours and the tempering to 400 ° C the resistance and wear resistance, while the impact resistance increases. And with the thermal treatment of tempering at 400 ° C for all the hardened specimens at 900 ° C at the time of study, the properties studied improved remarkably compared to the specimens only with tempering. It is concluded that the copper alloy - 10% aluminum responds well to the temple heat treatment and tempering, and that in the study conditions the temple time to 1 hour and the rest to 400 ° C is the most appropriate. Similarly, the temple time from 1 to 4 hours at 900 ° C and tempering at 400 ° C, significantly on the evaluated properties, according to the statistical analysis with a confidence level of 95%.